Zinc enrichment of whole potato tuber by vacuum impregnation - Erihemu (J Food Sci Technol, 2013)
Zinc is a nutritionally essential truce element, and thus zinc deficiency (ZD) severely affects human health. More than 25% of the world’s population is at risk of ZD. This study was initiated to examine the use of the vacuum impregnation (VI) technique for enriching zinc content of whole potatoes; the effect of vacuum time, restoration time, steam-cooking and storage at 4 °C on the zinc content of VI whole potatoes was evaluated. Whole potato tubers were immersed in a 9 g/100 g zinc (zinc gluconate) solution. Vacuum pressure of 1,000 Pa was applied for 0–120 min, and atmospheric pressure restoration for 0–4 h. Experimental results showed that the zinc content of VI potatoes increased with vacuum and restoration time. Moreover, VI-cooked unpeeled or peeled potatoes had 63–94 times and 47–75 times higher zinc contents than un-VI-cooked unpeeled or peeled potatoes, respectively. The world daily potato consumption (86 g) of the VI-cooked unpeeled and peeled potatoes provided adult men with 130–148% and 100–135% of the recommended daily allowance (RDA) of zinc, respectively. Also, the daily potato consumption of the unpeeled and peeled potatoes supplied adult women with 178–203% and 137–185% of the RDA level, respectively. In addition, the VI potatoes had 40 times higher zinc contents through 30 days of storage at 4 °C, compared with un-VI-treated potatoes. This study indicated that VI treatment of whole potatoes was useful for enriching the zinc content. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13197-013-1194-5) contains supplementary material, which is available to authorized users.